Flexural Performance of Concrete Reinforced by Plastic Fibers - Lakhiar, M. T.; Sohu, S.; Bhatti, I. A.; Bhatti, N.; Abbasi, S. A.; Tarique, M. (Engineering, Technology & Applied Science Research, 2018)
For sustainable development construction, recycle or reuse of waste materials is utilized. Many researchers conducted tried to create an innovative green concrete, utilizing waste materials. The aim of this research is to contribute and promote the use of plastic waste in concrete. The concrete’s flexural and workability were investigated by using different percentages of 0%, 0.2%, 0.4%, 0.6%, 0.8% and 1% of plastic fibers in concrete. In this study, M15 grade concrete beams were casted and cured for 7 and 28 days to analyze the flexural performance and workability. The outcomes demonstrated that the workability was slightly reduced by the utilizing plastic fibers where flexural strength improved by 16.5% at 0.6% addition of plastic fibers in concrete.